Impact of Clopidogrel on Mortality in Patients With Acute Heart Failure Stratified by Coronary Artery Disease: Findings From the Arabian Gulf Acute Heart Failure Registry (Gulf CARE). (November 2018) - Al-Zakwani, Ibrahim; Panduranga, Prashanth; Al-Lawati, Jawad A.; Sulaiman, Kadhim; Alsheikh-Ali, Alawi A.; AlHabib, Khalid F.; Suwaidi, Jassim Al; Al-Mahmeed, Wael; AlFaleh, Hussam; Alnobani, Omar; Al-Motarreb, Ahmed; Ridha, Mustafa; et al.
We evaluated the impact of clopidogrel use on 3- and 12-months all-cause mortality in patients with acute heart failure (AHF) stratified by coronary artery disease (CAD) in patients admitted to 47 hospitals in 7 Middle Eastern countries with AHF from February to November 2012. Clopidogrel use was associated with significantly lower risk of all-cause mortality at 3 months (adjusted odds ratio [aOR], 0.61; 95% confidence interval [CI]: 0.42-0.87; P = .007) and 12 months (aOR, 0.61; 95% CI: 0.47-0.79; P < .001). When the analysis was stratified by CAD, the clopidogrel group in those with AHF and CAD was also associated with significantly lower risk of all-cause mortality at 3 months (aOR, 0.56; 95% CI: 0.38-0.83; P = .003) and 12 months (aOR, 0.58; 95% CI: 0.44-0.77; P < .001). However, in AHF patients without CAD, clopidogrel use was not associated with any survival advantages, neither at 3 months (aOR, 0.99; 95% CI: 0.32-3.11; P = .987) nor at 12 months (aOR, 0.80; 95% CI: 0.37-1.72; P = .566). Clopidogrel use was associated with short- and long-term all-cause mortality in patients with AHF and CAD. In AHF patients without CAD, clopidogrel use did not offer any survival advantage.